2020
DOI: 10.52306/03010420gxuv5876
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Digital Divide: Comparing Information Security Behaviors of Generation Y and Generation Z Adults

Abstract: How individuals conceptualize their accountability related to digital technology. There may also be age-based vulnerabilities resulting from personal perceptions about the importance of engaging in best-practices. However, age may not be as critical as experience when it comes to implementation of these behaviors. Using the Cybersecurity Behaviors subscale of the Online Security Behaviors and Beliefs Questionnaire (OSBBQ), this study compared the self-reported cybersecurity attitudes and behaviors across colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This result can be explained by Generation X consumers being more risk-avoidant [32] and more experienced with financial services such as cashless payment [101]. In turn, digital natives (Generation Z) were not concerned about risks related to using digital devices that corroborates the finding of Debb et al [74].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This result can be explained by Generation X consumers being more risk-avoidant [32] and more experienced with financial services such as cashless payment [101]. In turn, digital natives (Generation Z) were not concerned about risks related to using digital devices that corroborates the finding of Debb et al [74].…”
Section: Discussionsupporting
confidence: 60%
“…This finding was somewhat surprising in the Generation X group since they claimed to be more risk-avoidant [32] and revealed higher perceived risk in mobile banking [73]. The result, however, is less striking for Generation Z because they tend to care less about privacy issues than Generation X [74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zers, as digital natives, rely much more on mobile technology for personal use than previous generations. Cybersecurity research confirmed that Generation Z adults tend not to pay attention to privacy policies, do not notice unusual computer performance or care less about antivirus and malware notifications (Debb et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%